Material with electron transmission function and preparation method and application thereof
By designing a material bridged by 9-alkyl-9-phenylfluorenyl and triazine groups, the problem that organic electroluminescent device materials in the prior art is difficult to have both electron transport and hole barrier properties, and the characteristics of low driving voltage, high luminous efficiency and long life are achieved.
Patent Information
- Application Number
- CN202411693675.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
AI Technical Summary
It is difficult for existing organic electroluminescent device materials to have good electron transport and hole blocking performance, resulting in less obvious improvement in the luminescence efficiency and lifetime of the device.
A material consisting of 9-alkyl-9-phenylfluorenyl bridging with aryl groups and triazine groups is designed, and its HOMO energy level is adjusted by connecting different substituents to achieve efficient electron transport and serve as a hole barrier layer or electron transport layer material.
It realizes the characteristics of low driving voltage, high luminous efficiency and long service life, significantly improving the performance of organic electroluminescent devices.
Smart Images

Figure CN119569670A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic electroluminescence, and in particular relates to a material with electron transport function and a preparation method and application thereof. Background Art
[0002] Organic Light-Emitting Diode (OLED) is a solid-state semiconductor device that uses organic materials to emit light under the action of an electric field. OLED is usually composed of multiple layers of organic thin films sandwiched between two electrodes, including a hole injection layer, a hole transport layer, a light-emitting auxiliary layer, an electron blocking layer, a light-emitting layer, an electron buffer layer, a hole blocking layer, an electron transport layer, an electron injection layer, a covering layer, etc.
[0003] The main function of the hole blocking layer is to prevent holes from moving from the light-emitting layer or active layer to the electron transport layer or cathode. By effectively blocking holes, it helps maintain the charge balance inside the device and prevents holes and electrons from recombining in the non-light-emitting area, thereby improving the luminescence efficiency of the device. Although the hole blocking layer mainly blocks holes, it also allows electrons to be transferred from the electron transport layer to the light-emitting layer. Therefore, the hole blocking layer usually also has good electron transport properties. The main function of the electron transport layer is to promote the efficient transfer of electrons from the cathode or electron injection layer to the light-emitting layer. A suitable electron transport layer can reduce the electron injection barrier and improve the electron injection efficiency. The hole blocking layer and the electron transport layer work together to ensure efficient and stable operation of OLEDs.
[0004] There are few materials that have both electron transport and hole blocking capabilities and excellent device performance, and the electron conduction rate of most materials is much lower than the hole conduction rate, so the life span and luminous efficiency of the prepared devices are not significantly improved. Therefore, designing and finding a stable and efficient compound as a new type of organic electroluminescent material to overcome its shortcomings in practical applications is the focus of research on organic electroluminescent device materials and the future research and development trend. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention discloses a material with electron transport function and a preparation method and application thereof.
[0006] It should be noted that the material structure with electron transport function disclosed in the present invention is composed of 9-alkyl-9-phenylfluorene groups bridged by aromatic groups and triazine groups. By connecting different substituents (aromatic groups, heteroaromatic groups or cyano-substituted aromatic groups or heteroaromatic groups), the HOMO energy level is within a suitable range, and the potential barrier between functional layers is effectively regulated to enable efficient electron transmission. As a hole blocking layer or electron transport layer material for an organic electroluminescent device, low driving voltage, high luminous efficiency and long service life characteristics are achieved.
[0007] In order to achieve the above objectives, the first object of the present invention is to provide a material with electron transport function, using the following technical solution:
[0008] A material having an electron transport function, having a chemical formula I structure:
[0009]
[0010] in,
[0011] R is independently selected from substituted or unsubstituted C1-C6 alkyl;
[0012] Ar1 is independently selected from hydrogen, substituted or unsubstituted benzene ring;
[0013] Ar2 is independently selected from substituted or unsubstituted benzene rings;
[0014] R1 and R2 are independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C6 alkyl;
[0015] n1 is independently selected from an integer from 1 to 3;
[0016] n2 is independently selected from an integer from 1 to 5;
[0017] p is independently selected from an integer of 1 or 2;
[0018] q is independently selected from an integer of 0 or 1;
[0019] Ar3 and Ar4 are each independently selected from the following structures:
[0020]
[0021] In the formula, * represents the connection point;
[0022] And, R3-R 14 are independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C6 alkyl;
[0023] n3、n 11 are independently selected from integers from 1 to 5;
[0024] n4 and n8 are independently selected from integers from 1 to 9;
[0025] n5, n6, n 13 are independently selected from integers from 1 to 13;
[0026] n7 and n9 are independently selected from integers from 1 to 7;
[0027] n 10 independently selected from integers from 1 to 8;
[0028] n 12 、n 14 are independently selected from integers from 1 to 11.
[0029] Furthermore, the chemical formula I has the following structures of chemical formulas IA to IE:
[0030]
[0031] Alternatively, R is independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, substituted or unsubstituted tert-butyl.
[0032] Optionally, R1-R 14 are independently selected from hydrogen, deuterium, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, and substituted or unsubstituted tert-butyl.
[0033] It should be noted that the substituent represented by "substituted" in the above-mentioned substituted or unsubstituted C1-C6 alkyl group is deuterium, and the substituent represented by "substituted" in the substituted or unsubstituted benzene ring is deuterium, methyl, ethyl, propyl, isopropyl, tert-butyl, tert-pentyl;
[0034] Furthermore, the above-mentioned material having electron transport function is selected from any one of the compounds represented by the following structural formulas:
[0035]
[0036]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047] The second object of the present invention is to provide a method for preparing the material having electron transport function as described above.
[0048] It should be noted that the material having electron transport function in the present invention can be prepared by methods known to those skilled in the art. Alternatively, the following reaction process is preferably used for preparation, and the specific operation is as follows:
[0049] (1) Adding raw material A (1.0 eq), diboronic acid pinacol ester (1.0-1.5 eq) and potassium acetate (2.0-4.0 eq) to a three-necked flask, then adding 1,4-dioxane, and then adding tri(dibenzylideneacetone)dipalladium (0.02-0.10 eq) and X-Phos (0.1-0.2 eq) under nitrogen, then heating to 120° C. and reflux for 5-20 hours; detecting the reaction by thin layer chromatography, after the reaction is completed, slightly lowering the temperature, filtering with diatomaceous earth to remove salt and catalyst, then adding water and dichloromethane to the filtrate for separation and extraction, retaining the organic phase for concentration, and purifying by column chromatography with a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) to obtain intermediate 1;
[0050] (2) Add intermediate 1 (1.0 eq), raw material B (1.0 eq) and potassium carbonate (2.0-4.0 eq) to a three-necked flask, then add a mixed solution of toluene, ethanol and water (V:V:V=3:1:1), then add tetrakis(triphenylphosphine)palladium (0.01-0.03 eq) under nitrogen, then heat to 80-95° C., and reflux for 1-10 hours; detect the reaction by thin layer chromatography, after the reaction is completed, slightly lower the temperature, filter with diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase and concentrate, and purify by column chromatography with a mixed solution of dichloromethane and petroleum ether (V:V=0:1, 1:4-1:10) to obtain intermediate 2;
[0051] (3) Add intermediate 2 (1.0 eq), diboronic acid pinacol ester (1.0-1.5 eq) and potassium acetate (2.0-4.0 eq) to a three-necked flask, then add 1,4-dioxane, and then add tri(dibenzylideneacetone)dipalladium (0.02-0.10 eq) and X-Phos (0.1-0.2 eq) under nitrogen, then heat to 120° C., and reflux for 5-20 hours; detect the reaction by thin layer chromatography, after the reaction is completed, slightly lower the temperature, filter with diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase, concentrate, and purify by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) to obtain intermediate 3;
[0052] (4) Add intermediate 3 (1.0 eq), raw material C (1.0 eq) and potassium carbonate (2.0-4.0 eq) to a three-necked flask, then add a mixed solution of toluene, ethanol and water (V:V:V=3:1:1), then add tetrakis(triphenylphosphine)palladium (0.01-0.03 eq) under nitrogen, then heat to 80-95° C., and reflux for 4-22 hours; detect the reaction by thin layer chromatography, after the reaction is completed, slightly lower the temperature, filter with diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase and concentrate, and purify by column chromatography using a mixed solution of dichloromethane and petroleum ether (1:4-1:10) to obtain chemical formula I;
[0053] The specific synthetic route is as follows:
[0054]
[0055] Wherein, R, Ar1-Ar4, R1-R2, n1-n2, p, q are as defined in chemical formula I, and Hal1 and Hal2 are independently selected from chlorine and bromine.
[0056] In particular, for complex raw materials that have not been disclosed before, classic Suzuki coupling reaction, lithiation reaction and / or dehydration reaction are used for synthesis and applied to the present invention.
[0057] The third object of the present invention is to provide an application of a material having an electron transport function, wherein the material having an electron transport function as described above is applied to an organic electroluminescent device.
[0058] Specifically, the organic electroluminescent device comprises an anode, a cathode and an organic layer disposed between the anode and the cathode.
[0059] It should be noted that the organic material layer of the organic electroluminescent device in the present invention may be formed as a single-layer structure or a multilayer structure having two or more organic material layers. For example, the organic electroluminescent device may have a structure including a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting auxiliary layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, etc. as organic material layers. However, the structure of the organic electroluminescent device is not limited thereto, and may include a smaller number of organic material layers or a larger number of organic material layers.
[0060] Specifically, the material with electron transport function described in the present invention can be used as a hole blocking layer material or an electron transport layer material of an organic electroluminescent device.
[0061] Further, the organic electroluminescent device can be used in an organic electroluminescent device, which includes but is not limited to a flat panel display, a computer monitor, a medical monitor, a television, a billboard, a light for internal or external lighting and / or signaling, a head-up display, a fully transparent or partially transparent display, a flexible display, a laser printer, a telephone, a mobile phone, a tablet, a photo album, a personal digital assistant (PDA), a wearable device, a laptop computer, a digital camera, a video camera, a viewfinder, a microdisplay, a three-dimensional display, a virtual reality or augmented reality display, a vehicle, a video wall including multiple displays tiled together, a theater or venue screen, a light therapy device and a sign.
[0062] Compared with the prior art, the present invention provides a material with electron transport function and a preparation method and application thereof, which have the following excellent effects:
[0063] The material compound disclosed in the present invention has good electron transport function, can be used as hole blocking layer or electron transport layer material of organic electroluminescent device, and can achieve low driving voltage, high luminous efficiency and long service life characteristics.
[0064] Specifically, 1) the 9-alkyl-9-phenylfluorenyl introduced into the material compound with electron transport function disclosed in the present invention is a structural unit with good electron transport ability, which can further optimize the electron transport performance of the material, and can effectively promote the migration of electrons from the cathode to the light-emitting layer. Its HOMO is relatively low, which helps to prevent holes from entering the electron transport layer or the cathode from the light-emitting layer or the hole transport layer; and triazine is a strong electron acceptor with high electron affinity, which can effectively attract and conduct electrons. The two are bridged by an aromatic group (phenyl or biphenyl) to form an efficient electron transport channel, which significantly improves the electron mobility of the entire material, thereby helping to improve the efficiency of the entire device;
[0065] 2) The material compound structure with electron transport function disclosed in the present invention also has good thermal stability, so that it maintains its structural integrity during the evaporation process, thereby effectively improving the life of the device; and the introduced cyanide group is a very strong electron acceptor, which can effectively attract and transport electrons, thereby improving electron mobility and effectively improving the efficiency of the device. The introduction of cyanide groups will also increase the rigidity of the molecule, which helps to improve the thermal stability of the material and can further extend the service life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0067] Figure 1 is the H NMR spectrum of compound 1. DETAILED DESCRIPTION
[0068] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the related drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] The invention specifically discloses a material with electron transport function and a preparation method and application thereof.
[0070] It should be noted that the numerical values given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value.
[0071] The specific embodiments described below are only part of the embodiments of the present application, rather than all the embodiments.
[0072] The features and performance of the present invention will be further described in detail below with reference to the embodiments.
[0073] Example 1
[0074]
[0075] The raw material C-1 is an existing technology and can be used directly, while the intermediate 1 is not an existing technology and needs to be synthesized in advance.
[0076] Raw material A-1 (1.1 eq, CAS number: 2921672-89-9), raw material B-1 (1.0 eq, CAS number: 475156-28-6) and potassium carbonate (3.0 eq) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V=3:1:1) was added, and then tetrakis(triphenylphosphine)palladium (0.01 eq) was added under nitrogen, and then the temperature was raised to 90°C, and refluxed for 4 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used to filter to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained for concentration, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used to purify by column chromatography to obtain intermediate 1 (yield: 78.9%).
[0077] In a three-necked flask, intermediate 1 (1.0 eq), pinacol diboron (1.5 eq) and potassium acetate (2.0 eq) were added, and then 1,4-dioxane was added, and then tri(dibenzylideneacetone)dipalladium (0.02 eq) and X-Phos (0.1 eq) were added under nitrogen, and then the temperature was raised to 120° C. and refluxed for 14 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained for concentration, and a mixed solution of dichloromethane and petroleum ether (V:V=1:4) was used for purification by column chromatography to obtain intermediate 2 (yield: 72.5%).
[0078] In a three-necked flask, intermediate 2 (1.0 eq), raw material C-1 (1.0 eq, CAS number: 1394937-38-2) and potassium carbonate (3.0 eq) were added, and then a mixed solution of toluene, ethanol and water (V:V:V=3:1:1) was added, and then tetrakis(triphenylphosphine)palladium (0.03 eq) was added under nitrogen, and then the temperature was raised to 95°C, and refluxed for 18 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained for concentration, and a mixed solution of dichloromethane and petroleum ether (V:V=1:5) was used for purification by column chromatography to obtain compound 1 (yield: 81.6%).
[0079] The obtained compound 1 was tested and analyzed, and the results were as follows:
[0080] HPLC purity: >99.8%.
[0081] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0082] Test value MS (ESI, m / Z): [M+H] + =716.39.
[0083] Elemental Analysis:
[0084] Calculated values: C, 88.92; H, 5.21; N, 5.87;
[0085] The test values are: C, 88.65; H, 5.38; N, 6.05.
[0086] H NMR spectrum: Figure 1 (Compound 1) shown.
[0087] Example 2
[0088]
[0089] The raw material A-2 is the same as the intermediate 2 in Example 1 and is directly used in the next step of synthesis.
[0090] Raw material A-2 (1.0 eq), raw material B-2 (1.1 eq, CAS number: 1936711-65-7) and potassium carbonate (3.0 eq) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and then tetrakis(triphenylphosphine)palladium (0.01 eq) was added under nitrogen, and then the temperature was raised to 90°C, and refluxed for 5 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used to filter to remove salt and catalyst, and then water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V = 1:6) was used to purify by column chromatography to obtain intermediate 1 (yield: 76.3%).
[0091] In a three-necked flask, intermediate 1 (1.0 eq), diboronic acid pinacol ester (1.5 eq) and potassium acetate (2.0 eq) were added, and then 1,4-dioxane was added, and then tri(dibenzylideneacetone)dipalladium (0.02 eq) and X-Phos (0.1 eq) were added under nitrogen, and then the temperature was raised to 120° C. and refluxed for 15 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained for concentration, and a mixed solution of dichloromethane and petroleum ether (V:V=1:4) was used for purification by column chromatography to obtain intermediate 2 (yield: 71.6%).
[0092] In a three-necked flask, intermediate 2 (1.0 eq), raw material C-2 (1.0 eq, CAS number: 1970122-69-0) and potassium carbonate (3.0 eq) were added, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and then tetrakis(triphenylphosphine)palladium (0.03 eq) was added under nitrogen, and then the temperature was raised to 95°C, and refluxed for 16 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used to filter to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained for concentration, and a mixed solution of dichloromethane and petroleum ether (V:V = 1:6) was used to purify by column chromatography to obtain compound 2 (yield: 81.0%).
[0093] The obtained compound 2 was tested and analyzed, and the results were as follows:
[0094] HPLC purity: >99.7%.
[0095] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0096] Test value MS (ESI, m / Z): [M+H] + =792.42.
[0097] Elemental Analysis:
[0098] Calculated values: C, 89.48; H, 5.22; N, 5.31;
[0099] The test values are: C, 89.20; H, 5.38; N, 5.48.
[0100] Example 3
[0101]
[0102] The raw material C-136 is the same as the intermediate 2 in Example 1 and is directly used in the next step of synthesis. Intermediate 1 is not a prior art and needs to be synthesized in advance.
[0103] Raw material A-136 (1.1 eq, CAS number: 2803479-44-7), raw material B-136 (1.0 eq, CAS number: 2756733-23-8) and potassium carbonate (3.0 eq) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V=3:1:1) was added, and then tetrakis(triphenylphosphine)palladium (0.01 eq) was added under nitrogen, and then the temperature was raised to 90°C, and refluxed for 5 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained for concentration, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used for purification by column chromatography to obtain intermediate 1 (yield: 77.7%).
[0104] In a three-necked flask, intermediate 1 (1.0 eq), raw material C-136 (1.0 eq) and potassium carbonate (3.0 eq) were added, and then a mixed solution of toluene, ethanol and water (V:V:V=3:1:1) was added, and then tetrakis(triphenylphosphine)palladium (0.03 eq) was added under nitrogen, and then the temperature was raised to 95°C, and refluxed for 19 hours; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used to filter to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, and the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used to purify by column chromatography to obtain compound 136 (yield: 80.7%).
[0105] The obtained compound 136 was tested and analyzed, and the results were as follows:
[0106] HPLC purity: >99.6%.
[0107] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0108] Test value MS (ESI, m / Z): [M+H] + =742.38.
[0109] Elemental Analysis:
[0110] Calculated values: C, 85.80; H, 4.76; N, 9.44;
[0111] The test values are: C, 85.53; H, 4.91; N, 9.61.
[0112] Example 4-76
[0113] The following compounds were synthesized by referring to the preparation methods of Examples 1 to 3 and tested using a Waters XEVOTQD mass spectrometer with low precision. The ESI source was used for testing, and the mass spectrometry test values are shown in Table 1 below.
[0114] Table 1 Mass spectrometry test values of Examples 4-76
[0115]
[0116]
[0117]
[0118] In addition, it should be noted that other compounds of the present invention can be obtained by referring to the preparation methods of the above-mentioned embodiments, so they are not listed one by one here.
[0119] Device Example 1: Preparation of organic electroluminescent device
[0120] The structure of the prepared OLED device is: ITO anode / HIL / HTL / Prime / EML / HBL / ETL / EIL / cathode / light extraction layer.
[0121] a. ITO anode: the coating thickness is The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate was cleaned in distilled water for 3 times, ultrasonically cleaned for 30 minutes, and then repeatedly cleaned with distilled water for 3 times, ultrasonically cleaned for 10 minutes. After washing, it was ultrasonically cleaned with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited thereon in sequence.
[0122] b. HIL (hole injection layer): The hole injection layer materials HT and P-dopant were vacuum evaporated at a deposition rate of 97:3, and the thickness was 10 nm. The chemical formula of the materials is shown below.
[0123] c. HTL (hole transport layer): At a deposition rate of , 130nm of HT was vacuum evaporated on the hole injection layer as a hole transport layer.
[0124] d. Prime (luminous auxiliary layer): At a deposition rate of , 5nm of Prime was vacuum-deposited on the hole transport layer as a light-emitting auxiliary layer.
[0125] e. EML (luminescent layer): At a evaporation rate of , a main material (Host) and a dopant material (Dopant) with a thickness of 30 nm are vacuum evaporated on the light-emitting auxiliary layer as a light-emitting layer. The chemical formulas of Host and Dopant are shown below, where the evaporation rate ratio of Host and Dopant is 98:2.
[0126] f. HBL (hole blocking layer): At a deposition rate of , compound 1 with a thickness of 5.0 nm was vacuum-deposited on the light-emitting layer as a hole blocking layer.
[0127] g. ETL (Electron Transport Layer): ET and Liq with a thickness of 30 nm were vacuum evaporated on the hole blocking layer as an electron transport layer, wherein the evaporation rate ratio of ET to Liq was 50:50.
[0128] h. EIL (electron injection layer): A Yb film layer with a thickness of 1.0 nm was vacuum-deposited on the electron transport layer at a deposition rate to form an electron injection layer.
[0129] i. Cathode: Magnesium and silver with a thickness of 13 nm were vacuum evaporated on the electron injection layer at a deposition rate ratio of 1:9 to obtain a cathode.
[0130] j. Light extraction layer: At a deposition rate of , CPL with a thickness of 65 nm was vacuum-deposited on the cathode as a light extraction layer.
[0131] K. Package the vapor-deposited substrate: First, use the glue coating equipment to coat the cleaned cover with UV glue, then move the coated cover to the pressing section, place the vapor-deposited substrate on the upper end of the cover, and finally bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue at the same time.
[0132]
[0133] Device Example 2-46
[0134] Referring to the method provided in the above device embodiment 1, the corresponding compounds in Table 2 were selected to replace compound 1, and the hole blocking layer was evaporated to prepare the corresponding organic electroluminescent devices, which were respectively recorded as device embodiments 2 to 46.
[0135] Device Comparison Examples 1-8
[0136] According to the method provided in the above device example 1, device comparative examples 1-8 were prepared respectively, except that the hole blocking layer (compound 1) in the device example 1 was replaced by the existing comparative compound ah, wherein the structural formula of compound ah is as follows:
[0137]
[0138] The driving voltage, BI value and lifespan of the organic electroluminescent devices obtained from the device embodiments 1 to 46 and the device comparative examples 1 to 8 were characterized at a brightness of 1000 (nits). The test results are shown in Table 2 below.
[0139] Table 2 Device test results
[0140]
[0141]
[0142] Device Example 47: Preparation of Organic Electroluminescent Device
[0143] The structure of the prepared OLED device is: ITO anode / HIL / HTL / Prime / EML / HBL / ETL / EIL / cathode / light extraction layer.
[0144] a. ITO anode: the coating thickness is The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate was cleaned in distilled water for 3 times, ultrasonically cleaned for 30 minutes, and then repeatedly cleaned with distilled water for 3 times, ultrasonically cleaned for 10 minutes. After washing, it was ultrasonically cleaned with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited thereon in sequence.
[0145] b. HIL (hole injection layer): The hole injection layer materials HT and P-dopant were vacuum evaporated at a deposition rate of 97:3, and the thickness was 10 nm. The chemical formula of the materials is shown below.
[0146] c. HTL (hole transport layer): At a deposition rate of 100%, 130nm of HT was vacuum-deposited on the hole injection layer as a hole transport layer.
[0147] d. Prime (luminous auxiliary layer): At a deposition rate of , 5nm of Prime was vacuum-deposited on the hole transport layer as a light-emitting auxiliary layer.
[0148] e. EML (luminescent layer): The host material (Host) and the dopant material (Dopant) with a thickness of 30nm are vacuum-deposited on the light-emitting auxiliary layer as the light-emitting layer. The chemical formulas of Host and Dopant are shown below. The evaporation rate ratio of Host and Dopant is 98:2.
[0149] f. HBL (hole blocking layer): At a deposition rate of , HB with a thickness of 5.0 nm was vacuum evaporated on the light-emitting layer as a hole blocking layer.
[0150] g. ETL (Electron Transport Layer): At a deposition rate of , compound 136 and Liq with a thickness of 30 nm were vacuum evaporated on the hole blocking layer as an electron transport layer, wherein the deposition rate ratio of compound 136 to Liq was 50:50.
[0151] h. EIL (electron injection layer): A Yb film layer with a thickness of 1.0 nm was vacuum-deposited on the electron transport layer at a deposition rate to form an electron injection layer.
[0152] i. Cathode: Magnesium and silver with a thickness of 13 nm were vacuum evaporated on the electron injection layer at a deposition rate ratio of 1:9 to obtain a cathode.
[0153] j. Light extraction layer: At a deposition rate of , CPL with a thickness of 65 nm was vacuum-deposited on the cathode as a light extraction layer.
[0154] K. Package the vapor-deposited substrate: First, use the glue coating equipment to coat the cleaned cover with UV glue, then move the coated cover to the pressing section, place the vapor-deposited substrate on the upper end of the cover, and finally bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue at the same time.
[0155]
[0156] Device Examples 48-76
[0157] Referring to the method provided in the above device embodiment 47, the corresponding compounds in Table 3 were selected to replace compound 136, and the electron transport layer was evaporated to prepare the corresponding organic electroluminescent devices, which were respectively recorded as device embodiments 48-76.
[0158] Device Comparison Examples 9-10
[0159] According to the method provided in the above device embodiment 47, device comparative examples 9-10 were prepared respectively, except that the organic electroluminescent device used the existing comparative compound ij to replace the electron transport layer (compound 136) in the above device embodiment 47 for evaporation. The chemical structure of the comparative compound ij is as follows:
[0160]
[0161] The driving voltage, BI value and life of the organic electroluminescent devices obtained from the device embodiments 47 to 76 and the device comparative examples 9 to 10 were characterized at a brightness of 1000 (nits). The test results are shown in Table 3 below:
[0162] Table 3 Device test results
[0163]
[0164]
[0165] Those skilled in the art know that in a blue top-emitting device, the luminous efficiency is greatly affected by chromaticity. Therefore, the influence of chromaticity on efficiency is taken into account, and the ratio of luminous efficiency to CIEy is defined as the BI value, that is, BI = (cd / A) / CIEy.
[0166]
[0167] The comparison compound a and compound 185 are parallel comparative examples, the difference between which is that the compound a is connected to a 9,9-dimethylfluorenyl group substituted with a phenyl group, while the compound 185 of the present invention is connected to a 9-methyl 9-phenylfluorenyl group. The introduction of the benzene ring at the 9th position of the fluorenyl group increases the π-conjugated system, making the electron cloud more dispersed, increasing the degree of conjugation of the entire molecule, reducing the driving voltage of the device, increasing the luminous efficiency, and reducing the HOMO energy level of the molecule, making it more difficult for holes to pass through this layer. The presence of the benzene ring also increases the rigidity of the molecule, making its structure more stable, making it less likely for the material to undergo structural changes during the evaporation process, and further enhancing the service life of the device.
[0168]
[0169] The comparative compounds d, e, and i are compounds in the patent CN117447414A previously studied by the applicant, and they are parallel comparative examples with compounds 2, 110, and 140, respectively. The difference between them is that the substituent (phenyl) below the 9-methyl 9-phenylfluorenyl group in the comparative compounds d, e, and i is connected to the benzene ring on the outside of the fluorene, while the substituent (phenyl) below the 9-methyl 9-phenylfluorenyl group in the compounds 2, 110, and 140 of the present invention is connected to the benzene ring on the inside of the fluorene, which increases the rigidity of the molecule, improves the thermal stability and chemical stability of the material, thereby enhancing the life of the device, and also makes the structure more densely stacked, which helps to improve the carrier transmission path and reduce energy loss. The inner side connected substituent benzene ring is also closer to the triazine side, which can significantly enhance the interaction between molecules and reduce its driving voltage.
[0170]
[0171] Comparative compound f and compound 109 are parallel comparative examples, the difference between them is that in comparative compound f, the triazine is connected to the 3-position of fluorene through a phenylene group, while the corresponding group in the present compound 109 is connected to the 2-position of fluorene, which is more compact and orderly than the structure connected to the 3-position, has a slightly higher color purity, and has improved molecular rigidity, thereby improving the thermal stability and chemical stability of the overall material, and slightly improving the performance of its device.
[0172]
[0173] Comparative compounds g, h and compounds 115, 116 are parallel comparative examples, respectively, the difference being that: there is no substituent below the 9-methyl-9-phenylfluorenyl in compounds 115 and 116 on comparative compounds g and h, while the 9-methyl-9-phenylfluorenyl in compounds 115 and 116 of the present invention contains a benzene ring as a substituent below, and the introduction of the benzene ring increases the π-conjugated system of the molecule, which contributes to more efficient hole injection and can also reduce the HOMO energy level of the molecule. The lower HOMO energy level makes it more difficult for holes to pass through this layer, thereby effectively preventing holes from moving from the light-emitting layer to the electron transport layer, thereby further improving the luminous efficiency of the device. In addition, the presence of the benzene ring increases the rigidity of the molecule, improves the thermal stability and chemical stability of the material, maintains the integrity of its structure during the evaporation process, and can further improve the service life of its device.
[0174] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A material having an electron transport function, characterized in that: The general structural formula of the material having electron transport function is shown in Chemical Formula I: in, R is independently selected from substituted or unsubstituted C1-C6 alkyl; Ar1 is independently selected from hydrogen, substituted or unsubstituted benzene ring; Ar2 is independently selected from substituted or unsubstituted benzene rings; R1 and R2 are independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C6 alkyl; n1 is independently selected from an integer from 1 to 3; n2 is independently selected from an integer from 1 to 5; p is independently selected from an integer of 1 or 2; q is independently selected from an integer of 0 or 1; Ar3 and Ar4 are each independently selected from the following structures: In the formula, * represents the connection point; And, R3-R 14 are independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C6 alkyl; n3、n 11 are independently selected from integers from 1 to 5; n4 and n8 are independently selected from integers from 1 to 9; n5, n6, n 13 are independently selected from integers from 1 to 13; n7 and n9 are independently selected from integers from 1 to 7; n 10 independently selected from integers from 1 to 8; n 12 、n 14 are independently selected from integers from 1 to 11.
2. The material having electron transport function according to claim 1, characterized in that: Chemical formula I has the following structures of chemical formulas IA to IE:
3. The material having electron transport function according to claim 1 or 2, characterized in that: R is independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, substituted or unsubstituted tert-butyl.
4. The material having electron transport function according to claim 1 or 2, characterized in that: R1-R 14 are independently selected from hydrogen, deuterium, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, and substituted or unsubstituted tert-butyl.
5. The material having electron transport function according to claim 1 or 2, characterized in that: The substituent represented by "substituted" in the substituted or unsubstituted C1-C6 alkyl group is deuterium, and the substituent represented by "substituted" in the substituted or unsubstituted benzene ring is deuterium, methyl, ethyl, propyl, isopropyl, tert-butyl, or tert-pentyl.
6. The material having electron transport function according to claim 1, characterized in that: The structure of the material having an electron transport function is selected from any one of the following compounds:
7. A method for preparing a material having an electron transport function as claimed in claim 1, characterized in that: The method specifically comprises the following steps: (1) Adding raw material A (1.0 eq), bipyraclostrobin (1.0-1.5 eq) and potassium acetate (2.0-4.0 eq) to a three-necked flask, then adding 1,4-dioxane, passing nitrogen, adding tri(dibenzylideneacetone)dipalladium (0.02-0.10 eq) and X-Phos (0.1-0.2 eq) under nitrogen protection, then heating to 120° C., and reflux reaction for 5-20 hours; detecting the reaction by thin layer chromatography, cooling after the reaction, filtering with diatomaceous earth to remove salt and catalyst, then adding water and dichloromethane to the filtrate for separation and extraction, retaining the organic phase and concentrating, and purifying by column chromatography with a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) to obtain intermediate 1; (2) Add intermediate 1 (1.0 eq), raw material B (1.0 eq) and potassium carbonate (2.0-4.0 eq) to a three-necked flask, then add a mixed solution of toluene, ethanol and water (V:V:V=3:1:1), then add tetrakis(triphenylphosphine)palladium (0.01-0.03 eq) under nitrogen, then heat to 80-95° C., and reflux for 1-10 hours; detect the reaction by thin layer chromatography, after the reaction is completed, cool, filter with diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase and concentrate, and purify by column chromatography with a mixed solution of dichloromethane and petroleum ether (V:V=0:1, 1:4-1:10) to obtain intermediate 2; (3) Add intermediate 2 (1.0 eq), diboronic acid pinacol ester (1.0-1.5 eq) and potassium acetate (2.0-4.0 eq) to a three-necked flask, then add 1,4-dioxane, pass nitrogen, add tri(dibenzylideneacetone)dipalladium (0.02-0.10 eq) and X-Phos (0.1-0.2 eq) under nitrogen protection, then heat to 120° C., and reflux for 5-20 hours; detect the reaction by thin layer chromatography, after the reaction is completed, cool, filter with diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase and concentrate, and purify by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) to obtain intermediate 3; (4) Add intermediate 3 (1.0 eq), raw material C (1.0 eq) and potassium carbonate (2.0-4.0 eq) to a three-necked flask, then add a mixed solution of toluene, ethanol and water (V:V:V=3:1:1), then add tetrakis(triphenylphosphine)palladium (0.01-0.03 eq) under nitrogen, then heat to 80-95° C., and reflux for 4-22 hours; detect the reaction by thin layer chromatography, after the reaction is completed, cool, filter with diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase and concentrate, and purify by column chromatography using a mixed solution of dichloromethane and petroleum ether (1:4-1:10) to obtain chemical formula I; The specific synthetic route is as follows: Wherein, R, Ar1-Ar4, R1-R2, n1-n2, p, q are as defined in Chemical Formula I of claim 1, and Hal1 and Hal2 are independently selected from chlorine and bromine.
8. Application of a material having electron transport function, characterized in that: The material with electron transport function as claimed in any one of claims 1 to 6 is applied to an organic electroluminescent device.
9. The use according to claim 8, characterized in that: The organic electroluminescent device comprises an organic layer; the organic layer comprises the material with electron transport function as claimed in any one of claims 1 to 6.
10. The use according to claim 9, characterized in that: The material having electron transport function can be used as both electron transport layer material and hole blocking layer material.